Progress in Life Cycle Assessment - Schebek, Liselotte; Herrmann, Christoph; Cerdas, Felipe (Sustainable Production, Life Cycle Engineering and Management, 2019)
The book contains the latest developments in the field of life cycle assessment (LCA) and its application. It contains numerous research articles from leading German research institutes working towards the further development of the methodology. The book provides important insights for professionals working in the field of sustainability assessment, for researchers interested in the current state of the research of the methodology and its application as well as for advanced university students in different science and engineering fields.